Impact of nonalcoholic fatty liver disease-related metabolic state on depression. (February 2023) - Ntona, Smaragda; Papaefthymiou, Apostolis; Kountouras, Jannis; Gialamprinou, Dimitra; Kotronis, Georgios; Boziki, Marina; Polyzos, Stergios A.; Tzitiridou, Maria; Chatzopoulos, Dimitrios; Thavayogarajah, Tharshika; Gkolia, Ioanna; Ntonas, Georgios; et al.
Abstract: Nonalcoholic fatty liver disease (NAFLD), also recently referred as metabolic (dysfunction)-associated fatty liver disease (MAFLD), is characterized by hepatocyte steatosis in the setting of metabolic risk conditions and in the absence of an underlying precursor, for instance alcohol consumption, hepatotropic viruses and hepatotoxic drugs. A possible association between NAFLD and depression has been proposed, owing to intersecting pathophysiological pathways. This narrative review aimed to summarize the current evidence that illustrate the potential pathophysiological and clinical linkage between NAFLD-related metabolic state and depression. Prefrontal cortex lesions are suggested to be a consequence of liver steatosis-associated systematic hyperinflammatory state, a phenomenon also occurring in depression. In addition, depressive symptoms are present in neurotransmitter imbalances. These abnormalities seem to be correlated with NAFLD/MAFLD, in terms of insulin resistance (IR), ammonia and gut dysbiosis' impact on serotonin, dopamine, noradrenaline levels and gamma aminobutyric acid receptors. Furthermore, reduced levels of nesfatin-1 and copine-6-associated BDNF (brain-derived neurotrophic factor) levels have been considered as a probable link between NAFLD and depression. Regarding NAFLD-related gut dysbiosis, it stimulates mediators including lipopolysaccharides, short-chain fatty acids and bile acids, which play significant role in depression. Finally, western diet and IR, which are mainstay components of NAFLD/MAFLD, are, also, substantiated to affect neurotransmitters in hippocampus and produce neurotoxic lipids that contribute to neurologic dysfunction, and thus trigger emotional disturbances, mainly depressive symptoms. Highlights: Nonalcoholic-fatty liver disease and depression share common pathogenetic mechanisms. Νeurotransmitters imbalance, insulin resistance and ammonia are mainly involved. Gut dysbiosis, bile acids, tryptophan, western diet are also implicated. Further studies will reveal the full association and aid optimal dual management.